2021
DOI: 10.1111/twec.13098
|View full text |Cite
|
Sign up to set email alerts
|

The China syndrome: A cross‐country evidence

Abstract: While in many advanced countries the increasing import competition from China on employment is a major concern for policymakers and the general public, its impact of Chinese import competition could be different across countries, depending upon the volume and the composition of the products. This paper examines the impact of the China shock on employment in six advanced countries. We find that the import penetration of final goods from China has negative effects on manufacturing employment in these countries, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The net effect on local CZ‐level employment from these two opposite effects is likely to be a net negative, which is in agreement with the establishment‐ and product‐level analyses by Hayakawa et al (2021), indicating that the direct and indirect propagated effects work even at the local labour‐market level. Moreover, our results complement those in the literature that find that intermediate imports from China may be favourable to the importing manufacturers (Kiyota et al, 2021; Taniguchi, 2019) by explicitly showing the positive downstream supply chain shock propagation. Further, our results provide additional evidence that intermediate imports are possibly a key factor distinguishing Japan from other countries, as we find that the trade structure between Japan and China may drive the difference between our results and the US case (Acemoglu, Autor, et al, 2016; Wang et al, 2018) in which positive downstream effect is observed primarily in non‐manufacturing sectors.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The net effect on local CZ‐level employment from these two opposite effects is likely to be a net negative, which is in agreement with the establishment‐ and product‐level analyses by Hayakawa et al (2021), indicating that the direct and indirect propagated effects work even at the local labour‐market level. Moreover, our results complement those in the literature that find that intermediate imports from China may be favourable to the importing manufacturers (Kiyota et al, 2021; Taniguchi, 2019) by explicitly showing the positive downstream supply chain shock propagation. Further, our results provide additional evidence that intermediate imports are possibly a key factor distinguishing Japan from other countries, as we find that the trade structure between Japan and China may drive the difference between our results and the US case (Acemoglu, Autor, et al, 2016; Wang et al, 2018) in which positive downstream effect is observed primarily in non‐manufacturing sectors.…”
Section: Discussionsupporting
confidence: 86%
“…34 Although our estimates of the composite employment consequences do not coincide with Taniguchi (2019), the implication from our downstream channel findings benefits from that study which shows that the positive employment effect of Chinese import penetration at the prefecture level comes from the imports of intermediate goods. It is further shown by Kiyota et al (2021) that this pattern is more widely applicable amongst developed countries. Our findings and those of Taniguchi (2019) together thus suggest that Japan-China trade, which involves larger intermediate inputs used in subsequent production, may work favourably for Japanese downstream manufacturing industries.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…While some firms will benefit from access to cheaper foreign inputs, others may face disruptions when their domestic suppliers succumb to import competition. Drawing on coarser data from the World Input-Output Database, Kiyota, Maruyama and Taniguchi (2021) show that supplier exposure to Chinese import competition from 2000 to 2014 caused only modest employment changes not only in US industries, but also in their counterparts in the UK and France. Instead, job gains in Germany were significant.…”
Section: The Impact Of Import Competition On Firms and Workersmentioning
confidence: 99%
“…Kiyota, Maruyama and Taniguchi (2021) estimate that the growth of imports of intermediate goods from China was 24% of the growth in total imports in the UK, 27% in the US, 31% in Germany and 36% in France, while more than two-thirds of South Korea's imports from China were intermediate rather than final goods.25 Adao, Arkolakis and Esposito (2020) observe that US local labour markets experienced differential declines in employment and wages when not only these regions themselves, but also their geographic neighbours, faced a large direct exposure to Chinese import competition. These geographic spillovers may partly reflect adverse demand spillovers along supply chains, where the contraction of industries in neighbouring regions reduces the demand for intermediate inputs produced by the supplier industries located in a region.…”
mentioning
confidence: 99%